Stimulasi Motorik Halus Melalui Kegiatan Melukis dengan Bahan Alam pada Anak Usia Dini di RA Ja-alhaq Kota Bengkulu - Fanisa, Nadia; Intan Rahayu, Putri; Widia Zafitri, Egi; Tamara, Pia; Ulum, Bakhrul (UIN Fatmawati Sukarno Bengkulu, 2025)
One of the aspects of development developed in early childhood education is physical motor development, one of which is fine motor. Fine motor development is developed so that children are able to move their fingers flexibly. This study was conducted to determine the development of fine motor skills in children, children's responses, difficulties faced by children, and obstacles faced by teachers at RA Ja-alHaq in the activities of providing stimulation of fine motor development in children through painting activities with natural materials. Descriptive is the method used in this research with a qualitative approach. Data collection techniques are observation, interview and documentation in this study. The subjects of this study were group B children at RA Ja-alHaq. with a total of 6 girls and 9 boys The data analysis technique used is narrative. In planning online learning in this study, it went well and received a good response from children and educators. Learning activities carried out online certainly have obstacles and difficulties faced by children, including children who still look difficult and stiff in moving their fine muscles. The obstacles faced by teachers are when online learning is an unsupportive signal and insufficient quota. So it can be concluded by researchers that painting with natural materials can stimulate children's fine motor skills.